GOOGLE TRANSLATE ERRORS ANALYSIS IN TRANSLATING NEWS FROM ENGLISH TO INDONESIAN - yanto yanto (Universitas Jambi, 2018)
The purpose of this research is to describe the errors found on Google Translate output in translating English news into Indonesian. This research focuses on ommision error, misordering, untranslated word, and confusion of sense resulted by Google Translate in translating the five English news into Indonesian. Those English news consists of different category such as bussiness, sport, technology, and national news. This research belongs to a qualitative research employing descriptive method. It aims to describe the errors made by Google translate, while the data of this research are the errors found on Google Translate in translating English news into Indonesian.In analyzing the errors, reseacher uses the taxonomy which was modified by Costa at all (2015). There are some errors found: The omission errors (5), misordering (18), untranslated word (19), and confusion sense (64) from the output. The analysis shows that confusion of sense is the dominant error produced by Google Translate in translating English news into Indonesian.